Shaping the ‘Other’: Foucauldian Insights Into Feminine Resistance in ‘Timbuktu’ - Alaoui Mhamdi, Nouh (International Journal of Language and Literary Studies, 2024)
This exploration delves into the complex portrayal of feminine resistance in Abderrahmane Sissako’s 2014 film "Timbuktu," framed within a Foucauldian perspective. Set against the backdrop of the jihadist occupation of Timbuktu, Mali, the film immerses viewers in a world where traditional village life collides with extremist ideologies, resulting in a complex interplay of power and resistance. The narrative unfolds with subtle undercurrents of oppression, as the occupying jihadists enforce their rigid interpretation of Sharia law on the local populace. Focusing on the character of Satima, the wife of the protagonist Kidane and Zabou, the shamanes, this analysis delves into different feminine resistance to conformity, driven either by honour or justice to challenge the oppressive norms imposed by the jihadists. Drawing inspiration from Michel Foucault’s discourse on power and resistance, this exploration reveals a rather multidirectional/multidimensional nature of feminine resistance. Satima’s refusal to comply with the sexual advances of Abdelkerim and Zabou’s enchantments and audacity vis-à-vis the jihadists provide insights into the transformative potential of marginalized voices. The film ultimately confronts the idea that some situations remain beyond an individual’s control, echoing an Old Testament-like sense of fate. Through an extraordinary long-take shot that captures the aftermath, the film underscores the limitations of power, even for those who seek to shape the "Other." This article thus invites a deeper examination of "Timbuktu," and feminine empowerment and agency in African cinema, shedding light on how resistance surpasses the confines of oppression, offering a gripping narrative of resilience in the face of extremism.